Stress-Strain Characteristic of Porous Asphalt Incorporating Cellulose Fiber - Nurul Syazni, Othman; Khairil Azman, Masri; Ahmad Kamil, Arshad; Putra Jaya, Ramadhansyah; Mohd Rosli, Mohd Hasan (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Porous asphalt (PA) is a type of asphalt mixture that has large air void content to increase the drainage capability of flexible pavement. However, PA suffers a few drawbacks such as less durable and less tensile strength due to large air void characteristic. Thus, this study intended to utilize cellulose fiber to increase the overall performance of PA. Cellulose fiber (CF) used were in the range of 0.2% to 0.6% by weight of PA mixture. Among the tests involve to analyze the overall performance of CF modified PA were Abrasion Loss, Marshall Stability, Resilient Modulus and Dynamic Creep. From data analysis, it shows that 0.4% CF significantly increased the abrasion resistance. Meanwhile, highest stability and resilient modulus values obtained at 0.6% CF-PA. From the results, it shows that the addition of CF can significantly enhance the overall performance of PA.